Research on the influence of g-C3N4 microstructure changes on the efficiency of visible light photocatalytic degradation - Hong Tu; Bihong Tian; Zhichao Zhao; Renjiang Guo; Ya Wang; Shunhong Chen; Jian Wu (Water Research X)
The structural modulation of pristine graphitic carbon nitride poses a considerable challenge in the rational design of catalysts for the efficient degradation of small organic pollutants under visible light. In this study, we combined first-principles calculations and the structure-function relationship to predict a high-performance catalyst. The results reveal that CN-8 demonstrates a remarkable degree of electron-hole separation. Notably, CN-8 shows exceptional degradation efficiency towards rhodamine B, tetracycline, bisphenol A, and fluralaner under visible light irradiation. Specifically, the degradation rate constants are 11, 4, 12, and 32 times higher, respectively, compared to bulk g-C3N4. Through density functional theory calculations and investigations of the structure-function relationship, it is confirmed that the superior catalytic activity of CN-8 lies in modifying the amino position, which alters the electron cloud distribution and promotes the efficient separation of photo-generated electron-hole pairs. This study provides valuable insights for the development of eco-friendly and efficient photocatalysts for environmental remediation.